⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ 2 x 3 = 1 + 3 2 y + 1 2 y 3 = 1 + 3 2 x + 1 Given the system of equations above, find x + y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can clearly see that f (x)=f (inverse) of y {where f (x)=2x^3-1}.
Similarly f (y)=f (inverse) of x.
Thus f (f (f (x)))=x.
Now (f (x))<x if x <1.
And f (x)>x if x>1 thus.
f (f....f (x)))..))<x if x <1 and so is greater .
than x part is proved.
And thus only soln for x is x=1.
And for this y=1 satisfies.
thus x+y=2
Is this the only solution?
Problem Loading...
Note Loading...
Set Loading...
Assuming x is real...
Set f ( u ) = 2 u 3 − 1 . Then the given system is equivalent to { y = f ( f ( x ) ) x = f ( f ( y ) ) and therefore f ( f ( f ( f ( x ) ) ) ) = x .
We note that f is strictly increasing, so by repeated application of f , we see f ( x ) < x f ( x ) > x ⟹ f ( f ( f ( f ( x ) ) ) ) < f ( f ( f ( x ) ) ) < f ( f ( x ) ) < f ( x ) < x ⟹ f ( f ( f ( f ( x ) ) ) ) > f ( f ( f ( x ) ) ) > f ( f ( x ) ) > f ( x ) > x so that we must have f ( x ) = x .
That is, 2 x 3 − 1 = x 2 x 3 − x − 1 = 0 ( x − 1 ) ( 2 x 2 + 2 x + 1 ) = 0 showing that the only real solution is x = 1 .
This gives y = f ( f ( 1 ) ) = 1 and therefore x + y = 2